Affirmative Action: Lessons to Be Learned from the United States' Experience? - Kersten, Astrid (Kvinder, Køn & Forskning, 1999)
Bidraget er ikke tilgængeligt elektronisk. Abstract: This article discusses the issue of Affirmative Action, as it has been implemented in the US context over the past 35 years. It explores the legal and operational nature of AA in the US, its accomplishments with regard to improving the status of women in the US workforce, and alternative ways in which AA can be applied effectively in the European context. Is is argued that AA is both a useful and necessary tool for combatting gender discrimination in the workplace - without AA, basic issues of accountability and progress are very difficult to operationalize, leaving the goal of equal employment opportunity in the realm of idealistic abstraction. Should European contries decide to use AA, the U.S. experience can provide many useful lessons regarding the need for education, the need for a proper legislative framework, and the need to supplement this legislation with internal company development efforts.